PDCD10 promotes proliferation, migration, and invasion of osteosarcoma by inhibiting apoptosis and activating EMT pathway. (18th July 2022) - Xu, Ke; Fei, Wenchao; Huo, Ziqi; Wang, Shuoer; Li, Yinghua; Yang, Gong; Hong, Yang
Abstract: Background: Osteosarcoma, a common primary malignant tumor, occurs in children and adolescents with a poor prognosis. The current treatment methods are various, while the five‐year survival rate of patients has not been significantly improved. As a member of the programmed death factor (PDCD) family, programmed death factor 10 (PDCD10) plays a role in regulating cell apoptosis. Several studies of PDCD10 in CCM and cancers have been reported before. However, there are no relevant research reports on the effects of PDCD10 on osteosarcoma. Methods: We used bioinformatics analysis, IHC, and clinical data to confirm the expression of PDCD10 and its correlation with prognosis in osteosarcoma. Then, we used shRNAs and cDNA to knock down or overexpress PDCD10 in U2OS and MG63 cell lines. A series of function assays such as CCK8, Wound healing test, Plate cloning formation assay, and Transwell were done to confirm how PDCD10 affects osteosarcoma. Animal assays were done to confirm the conclusions in cell lines. At last, WB was used to measure the protein expression levels of apoptosis and the EMT pathway. Results: PDCD10 was highly expressed in patients with osteosarcoma and correlated with prognosis; PDCD10 knockdown inhibited osteosarcoma growth, proliferation, migration, and invasion; PDCD10 overexpression promoted osteosarcoma growth, proliferation, migration, and invasion. In vivo experiments confirmed the conclusions in cell lines; PDCD10 inhibited apoptosis and activated the EMT pathway. Conclusions: In this study, it was found that PDCD10 was highly expressed in patients with osteosarcoma, and it was closely related to patient prognosis. PDCD10 inhibited tumor cell apoptosis and promoted tumor progression by activating the EMT pathway. These findings may provide a potential target for gene therapy of osteosarcoma. Abstract : In this study, it was found that PDCD10 was highly expressed in patients with osteosarcoma, and it was closely related to patient prognosis. PDCD10 inhibited tumor cell apoptosis and promoted tumor progression through activating EMT pathway. These findings may provide a potential target for gene therapy of osteosarcoma.